2017
DOI: 10.1007/s00417-017-3587-z
|View full text |Cite
|
Sign up to set email alerts
|

Two- and three-dimensional topographic analysis of pathologically myopic eyes with dome-shaped macula and inferior staphyloma by spectral domain optical coherence tomography

Abstract: Vertical and horizontal OCT sectional scanning in combination with three-dimensional macular map reconstruction provides important information for understanding the posterior anatomical structure of dome-shaped macula and inferior staphyloma in pathologically myopic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 37 publications
1
9
1
1
Order By: Relevance
“…Contour abnormalities of the choroid and sclera are well seen using EDI and SS OCT, and even more so in high myopia where the penetration is deeper due to the thinner choroid and relatively depigmented RPE. These include posterior staphyloma,[ 96 97 98 ] dome-shaped macula. [ 60 99 100 101 ] peripapillary and macular intrachoroidal cavitations,[ 61 62 ] and optic pits and colobomas[ 102 103 104 ]…”
Section: Choroidal Imagingmentioning
confidence: 99%
“…Contour abnormalities of the choroid and sclera are well seen using EDI and SS OCT, and even more so in high myopia where the penetration is deeper due to the thinner choroid and relatively depigmented RPE. These include posterior staphyloma,[ 96 97 98 ] dome-shaped macula. [ 60 99 100 101 ] peripapillary and macular intrachoroidal cavitations,[ 61 62 ] and optic pits and colobomas[ 102 103 104 ]…”
Section: Choroidal Imagingmentioning
confidence: 99%
“…Some studies have reported DSM could be seen in eyes with PS Type I, II, III, V, or IX. 9 , 13 In fact, there were also several studies about 3D OCT macular map reconstruction, 9 , 14 , 15 and three DSM patterns were observed, that is, vertical oval-shaped dome, horizontal oval-shaped dome, and round dome. But when it comes to the location relationship between DSM and PS, it seems that researchers preferred to express that DSM is located in a deep staphyloma, weakening the exact correspondence between them.…”
Section: Discussionmentioning
confidence: 92%
“…These results were similar to those previous reports. 9 , 15 , 17 , 18 Two-thirds of the DSM had positive 3D-MRI findings. Nine eyes had horizontal oval-shaped dome, and a band-shaped inward convexity that extended horizontally from the optic disc through the fovea could be seen on 3D MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Современные спектральные томографы позволяют глубоко и дифференцировано сканировать и визуализировать хориоидею и склеру с возможностью измерения их толщины. Данные приборы позволяют выполнять 2D-и 3D-ОКТ-реконструкцию заднего полюса, что важно для понимания анатомического строения заднего полюса глаза в целом и макулярной области в частности [20]. При КМ линия пигментного эпителия куполообразно приподнята, под ней визуализируется вся сосудистая оболочка, видна ее граница со склерой, толщина сосудов хориоидеи может быть неравномерной, с локальными участками истончения и, наоборот, увеличения в зоне купола [21].…”
Section: результаты и обсуждениеunclassified